ACO-based enhanced energy-efficient intelligent routing protocol for MANET. (4th June 2020) - Jayalakshmi, P.; Saravanan, R.
Mobile ad hoc Network (MANET) consists of a group of mobile nodes and the communication among them is done without any supporting centralised structure. Routing in MANETs is a difficult because of their dynamic features such as high mobility, constrained bandwidth and link failures due to energy loss. The objective of this work is to implement an intelligent routing protocol by selecting efficient nodes for routing the information. To provide good throughput in the network, Ant Colony Optimisation (ACO) based enhanced energy-efficient intelligent routing is proposed. Selecting the best intermediate hop for intelligent routing includes ACO technique which greatly reduces the network delay and link failures by validating the coordinator nodes. Coordinator nodes are picked by validating their metrics and Best Coordinator Nodes (BCN) are selected among them as good intermediate hops for intelligent routing. The performance is evaluated for the proposed protocol and the metrics considered for evaluation are delivery and loss rate of sent data, throughput and lifetime of the network, delay and energy consumption.